2015
DOI: 10.1038/ncomms9472
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells use extracellular vesicles to outsource mitophagy and shuttle microRNAs

Abstract: Mesenchymal stem cells (MSCs) and macrophages are fundamental components of the stem cell niche and function coordinately to regulate haematopoietic stem cell self-renewal and mobilization. Recent studies indicate that mitophagy and healthy mitochondrial function are critical to the survival of stem cells, but how these processes are regulated in MSCs is unknown. Here we show that MSCs manage intracellular oxidative stress by targeting depolarized mitochondria to the plasma membrane via arrestin domain-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
778
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 789 publications
(818 citation statements)
references
References 66 publications
37
778
2
1
Order By: Relevance
“…Furthermore, our pathway analysis identified mitochondrial dysfunction and oxidative phosphorylation among the top canonical pathways. Cells have been found to shed lysosome‐like vesicles and entire mitochondria into EVs through a mitophagy‐dependent mechanism (Phinney et al., 2015). In fact, mesenchymal stem cells use this mechanism to release mitochondria in EVs in response to oxidative stress (Phinney et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our pathway analysis identified mitochondrial dysfunction and oxidative phosphorylation among the top canonical pathways. Cells have been found to shed lysosome‐like vesicles and entire mitochondria into EVs through a mitophagy‐dependent mechanism (Phinney et al., 2015). In fact, mesenchymal stem cells use this mechanism to release mitochondria in EVs in response to oxidative stress (Phinney et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Cells have been found to shed lysosome‐like vesicles and entire mitochondria into EVs through a mitophagy‐dependent mechanism (Phinney et al., 2015). In fact, mesenchymal stem cells use this mechanism to release mitochondria in EVs in response to oxidative stress (Phinney et al., 2015). Here, perhaps the higher levels of mitochondrial RNAs in serum with age may be a consequence of mitochondrial dysfunction and higher levels of oxidative stress that occur with age.…”
Section: Discussionmentioning
confidence: 99%
“…MSC-derived EVs alone are capable of recapitulating many of the beneficial effects of MSC whole-cell therapy (25)(26)(27)(28). Phinney and colleagues observed the transfer of MSC mitochondria and miRNAs via EVs to human macrophages in a model of silicosis and found that mitochondria enhanced macrophage bioenergetics, whereas miRNAs suppressed Toll-like receptor signaling (24). They observed that normoxia (21% oxygen) induced oxidative stress, thereby promoting mitophagy in MSCs.…”
mentioning
confidence: 99%
“…Recently, EVs have emerged as an important component of the MSC secretory repertoire. MSC-derived EVs may contain a diverse cargo, including proteins, mRNAs, microRNAs (miRNAs), and mitochondria, the functional effects of which remain largely unknown (9,(23)(24)(25). MSC-derived EVs alone are capable of recapitulating many of the beneficial effects of MSC whole-cell therapy (25)(26)(27)(28).…”
mentioning
confidence: 99%
“…As another example, MSC EVs are also successfully investigated in refractory graft-versus-host disease [99]. The exact mechanism behind the therapeutic effect of MSC-derived EVs remains largely obscure and is a topic of intensive investigation [100]. It is however known that stem cell EVs are enriched in signaling proteins, including cytokines, chemokines, interleukins and growth factors [101].…”
Section: Harnessing the Intrinsic Biological Effect Of Evsmentioning
confidence: 99%